2023
DOI: 10.1186/s12951-023-01847-w
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional porous poly (L-lactic acid) nanofiber membranes with enhanced anti-inflammation, angiogenesis and antibacterial properties for diabetic wound healing

Abstract: With increased diabetes incidence, diabetic wound healing is one of the most common diabetes complications and is characterized by easy infection, chronic inflammation, and reduced vascularization. To address these issues, biomaterials with multifunctional antibacterial, immunomodulatory, and angiogenic properties must be developed to improve overall diabetic wound healing for patients. In our study, we prepared porous poly (L-lactic acid) (PLA) nanofiber membranes using electrospinning and solvent evaporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…For example, polylactic acid (PLA), a hydrophobic and thermally stable aliphatic polyester that biodegrades into non-toxic natural lactic acid, has been widely used in biomedical applications. PLA can be used alone or in combination with other small molecules or polymers for cartilage and joint regeneration [ 24 , 25 ], drug delivery and release [ 26 , 27 ], wound healing [ 28 , 29 ] and other therapies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Other biodegradable polymers, including poly(lactide-co-glycolic acid) (PLGA), poly(vinyl alcohol) (PVA), poly(ε-caprolactone) (PCL), poly(glycolic acid) (PGA), poly(3-hydroxybutyrate) (PHB), poly(ethylene glycol) (PEG) and PPC ( Figure 1 ) [ 37 , 38 , 39 ], have also been applied in healthcare.…”
Section: Biomaterials Based On Synthetic Polymersmentioning
confidence: 99%
“…For example, polylactic acid (PLA), a hydrophobic and thermally stable aliphatic polyester that biodegrades into non-toxic natural lactic acid, has been widely used in biomedical applications. PLA can be used alone or in combination with other small molecules or polymers for cartilage and joint regeneration [ 24 , 25 ], drug delivery and release [ 26 , 27 ], wound healing [ 28 , 29 ] and other therapies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Other biodegradable polymers, including poly(lactide-co-glycolic acid) (PLGA), poly(vinyl alcohol) (PVA), poly(ε-caprolactone) (PCL), poly(glycolic acid) (PGA), poly(3-hydroxybutyrate) (PHB), poly(ethylene glycol) (PEG) and PPC ( Figure 1 ) [ 37 , 38 , 39 ], have also been applied in healthcare.…”
Section: Biomaterials Based On Synthetic Polymersmentioning
confidence: 99%
“…In vitro cell testing results demonstrated that the PLA/SCS/PDA-GS membrane could immunomodulate macrophages toward M2 phenotype development. Moreover, the PLA nanofiber membrane containing SCS also exhibited an enhanced potential for promoting macrophage-to-fibroblast transdifferentiation [ 215 ].…”
Section: Application Of Nanofibrous Scaffolds In Wound Healingmentioning
confidence: 99%
“…Gentamicin was loaded into the middle hydrogel layer, exerting its antibacterial activity through natural release, while the outer nanofiber layers of the hydrogel act as diffusion barriers, reducing the initial burst release of gentamicin (15–30%) [ 234 ]. Hao Yu et al modified poly(L-lactic acid) (PLA) porous nanofiber membranes by incorporating polydopamine–gentamicin (PDA-GS) and sulfated chitosan (SCS), promoting the controlled release of GS through dopamine self-polymerization to prevent early wound infection [ 215 ].…”
Section: Application Of Nanofibrous Scaffolds In Wound Healingmentioning
confidence: 99%
“…PLA is an aliphatic polyester that is easily obtained in an eco-friendly way through the condensation of lactic acid, followed by the ring-opening polymerization of cyclic lactides [ 68 , 118 , 136 , 137 ]. Its good biocompatibility, biodegradability, and relatively high mechanical properties make PLA an appealing material for biomedical applications [ 68 , 118 , 119 ].…”
Section: Biomaterials As a Promising Therapeutic Platform For Wound D...mentioning
confidence: 99%